Karyotype Analysis of Three Species of Pinus - Dhillon, Sukhraj S. (Indian Forester, 1973)
Karyotypes have been reported for three species of Pinus, namely P. lambertiana, P. rigida and P. radiata. All three species have the shortest pair (12th) with heterobrachial arms. These results confirm the general karyotypic pattern described for most of the species belonging to the genus Pinus. Comparision of 11th and 12th pair indicates a greater tendency of 11th pair towards a heterobrachial condition in P. lambertiana. P. lambertiana and P. rigida showed no chromosomes to be secondarily constricted and P. radiata showed one pair of chromosomes to be secondarily constricted. The present as well as previous conflicting reports suggest, however, a more thorough study of secondary costriretion behaviour is needed. Magnitude of difference in chromosome length between 1st and 12th pair is also described in these species.